2003
DOI: 10.4049/jimmunol.170.4.2053
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4 T Cell Help and Costimulation in CD8 T Cell Responses During Listeria monocytogenes Infection

Abstract: CD4 T cells are known to assist the CD8 T cell response by activating APC via CD40-CD40 ligand (L) interactions. However, recent data have shown that bacterial products can directly activate APC through Toll-like receptors, resulting in up-regulation of costimulatory molecules necessary for the efficient priming of naive T cells. It remains unclear what role CD4 T cell help and various costimulation pathways play in the development of CD8 T cell responses during bacterial infection. In this study, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
136
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 77 publications
7
136
2
Order By: Relevance
“…It might therefore be possible that HKLM immunization does not induce sufficient 4-1BBL up-regulation on CD11c hi DC to fully activate CD8 + T cells. In support of this, a recent study using 4-1BBL-deficient mice suggested impaired CD8 + T cell activation following L. monocytogenes infection [23].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It might therefore be possible that HKLM immunization does not induce sufficient 4-1BBL up-regulation on CD11c hi DC to fully activate CD8 + T cells. In support of this, a recent study using 4-1BBL-deficient mice suggested impaired CD8 + T cell activation following L. monocytogenes infection [23].…”
Section: Discussionmentioning
confidence: 76%
“…6) supports the hypothesis that killed bacteria do not fully activate DC. It has been shown in vitro that live bacteria are far more potent in activating bone marrow-derived DC than are HKLM [23]. This favors the idea that HKLM and live bacteria differentially activate DC in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…The costimulatory role of TNFR2 during LM infection appears similar to CD28: CD28 Ϫ/Ϫ mice possess reduced LM-specific CD8 T cell responses, compared with WT mice, but differentiation into effector T cells is intact (11,12). Moreover, CD28 Ϫ/Ϫ mice exhibited increased susceptibility to LM as evidenced by persistent bacterial load even up to day 7 p.i.…”
Section: Discussionmentioning
confidence: 84%
“…3 CD28-deficient mice have reduced LM-specific CD8 T cell responses, compared with wild-type (WT) mice, but differentiation into effector and memory T cells appears intact (11), suggesting that CD28 sets a critical threshold for the accumulation of LM-specific CD8 T cells. Mice that lack CD137 ligand (4-1BB ligand) also display diminished activation of CD8 T cells, compared with WT mice (12). Thus, costimulation mediated by members of two distinct superfamilies of receptors provides multiple checkpoints in the differentiation program that confers flexibility in the adaptive immune response.…”
mentioning
confidence: 99%
“…Such a cell population, which could be re-expanded out of a small pool of central memory T cells within a short period of time after antigen reencounter, may not need to be maintained at high frequencies. Three observations in the bacterial infection model support this hypothesis: (1) Despite decreasing numbers of bacteria-specific CD4 + memory T cells, the quality of protective immunity is not negatively affected; even after complete depletion of CD4 + T cells following primary infection, CD8 + Listeria-specific memory T cells are maintained and mediate effective protective immunity [32]. Interestingly, depletion of CD4 + T cells actually enhances the CD8 + memory T cell response [33].…”
Section: Discussionmentioning
confidence: 90%